Corporate restructuring and its wealth effects: the case of Lion Group - Mat Nor, Fauzias; Alias, Norazlan; Yaacob, Mohd Hasimi (Universiti Utara Malaysia, 2007)
This case study evolves around four announcements related to a specific corporate restructuring proposal. The primary reason for the corporate restructuring is to restructure the debt of six companies: Lion Industries(LICB), Silverstone (SCB), Amsteel Corp Berhad (ACB), Lion Corporation(LCB), Lion Forest Industries (LFI), and Lion Diversified Holding Berhad(LDH). The track record of the companies revealed that these companies have been heavily levered causing them to be financially risky and therefore, highly sensitive to any economic shocks, let alone a fatal financial typhoon like the 1997 economic crisis. As at the end of the study period on June 30, 2003, that is, more than three years after the initial announcement of the proposed corporate restructuring, the plan has yet to be completed. Nonetheless, the present study had managed to produce some interesting results. By applying the common event-study approach, the results indicated that information about the restructuring plan has been significantly conveyed to the market in each restructuring announcement. Generally, the market regards all announcements in event window (-1,+1) unfavourably.